How the new international goal for child mortality is unfair to sub-Saharan Africa (again) - Simon Lange; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
The post-2015 development includes level-end goals for both under-five and neonatal mortality to be obtained by 2030: no more than 25 and 12 deaths per 1,000 births, respectively. Recent accelerations in the rate of reduction in under-five mortality have been cited as a cause for optimism. In this paper, we show that changes in mortality rates are subject to mean reversion. Hence, high rates observed recently for Sub-Saharan Africa make for an overly optimistic estimate of future reductions. Taking this into account in projecting mortality rates until 2030, we find that only very few countries in Sub-Saharan Africa are likely to attain the new targets while a majority of countries elsewhere are likely to attain the target or have done so already. We also show that while MDG4 has been rightly criticized as `unfair' to Sub-Saharan Africa in the past, a relative target may have been more appropriate today and would be relevant for all countries. We also offer a discussion of likely challenges the region faces in making further inroads against preventable deaths.
Keywords: I15; I18; J11; J18; O21; 330; MDGs; SDGs; under-five mortality; Sub-Saharan Africa